2018
DOI: 10.1021/acscatal.8b00468
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Chromium-Catalyzed Ethylene Trimerization

Abstract: The kinetics of ethylene trimerization by a chromium N-phosphinoamidine (Cr-(P,N)) precatalyst activated by modified methylaluminoxane (MMAO) has been investigated by high-pressure NMR techniques. An in-depth kinetic analysis of this metallacyclic mechanism has been conducted. It was found that an intermediate in the trimerization catalytic cycle, proposed in this study as the chromium alkenyl hydride species, degrades into a polymer active site where this degradation step is independent of ethylene concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 35 publications
6
24
0
Order By: Relevance
“…These observations lead to two hypotheses: i) either the first ethene coordination event is endergonic in nature and coordination of ethene cannot be observed in the experiment as performed or ii) a minority species is responsible for catalysis and the majority species is incapable of coordinating ethene. The first hypothesis is in line with a recent kinetic study of a {Cr(PN)} ethene tetramerization system, where it is demonstrated that the first and/or the second ethene coordination event is reversible . The second hypothesis has been proposed by Bercaw and coworkers in a {Cr(PNP)} ethene trimerization system …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…These observations lead to two hypotheses: i) either the first ethene coordination event is endergonic in nature and coordination of ethene cannot be observed in the experiment as performed or ii) a minority species is responsible for catalysis and the majority species is incapable of coordinating ethene. The first hypothesis is in line with a recent kinetic study of a {Cr(PN)} ethene tetramerization system, where it is demonstrated that the first and/or the second ethene coordination event is reversible . The second hypothesis has been proposed by Bercaw and coworkers in a {Cr(PNP)} ethene trimerization system …”
Section: Resultssupporting
confidence: 80%
“…The first hypothesis is in line with a recent kinetic study of a {Cr (PN)} ethene tetramerization system, where it is demonstrated that the first and/or the second ethene coordination event is reversible. [31] The second hypothesis has been proposed by Bercaw and coworkers in a {Cr(PNP)} ethene trimerization system. [32] To investigate the first hypothesis, we resorted to different substrates.…”
Section: Spectroscopic Investigation Of the Activation Process In Thementioning
confidence: 98%
“…The origin of the selectivity towards ethylene trimerization shown with a number of chromium catalysts (see section 3) is considered to take place by metallacyclic-based mechanism, as initially proposed by Manyik [151], later modified by Briggs [152] and by a number of subsequent studies (Scheme 2) [153][154][155]. The first step of the catalytic cycle is to cis-coordinate two ethylene molecules to the metal center, which then undergoes oxidative cyclization to form a chromacyclopentane.…”
Section: Tri-/tetramerization Of Ethylenementioning
confidence: 99%
“…Herein, we report another type of MAO‐free and extremely active catalytic system, whose activity is more than 10 times that of the original MAO‐based Sasol system. Catalyst development for ethylene oligomerization is still an active research topic in both academia and industry …”
Section: Introductionmentioning
confidence: 99%